The relationship between prenatal care and adherence to treatment for Congenital Syphilis from 2018 to 2021 (Research, Society and Development, 2023)
Objective: To identify and analyze the number of notifications of congenital syphilis cases discovered through the presence or absence of prenatal care and also the adherence or non-adherence to partner treatment. Method: A cross-sectional, observational and descriptive study with a quantitative approach, which included cases of congenital syphilis, comparing whether prenatal care and partner treatment were carried out or not between the years 2018 and 2021, using data collected from DATASUS. Result: In the period under study, a total of 82,194 cases of congenital syphilis were noted, with the highest number of cases in 2018, in these 4 years, 50,441 pregnant women with syphilis underwent prenatal care and within this number, in 35,046 of these cases the partner did not receive adequate treatment, an alarming figure of approximately 69.5%. Conclusion: it is noted that prenatal care does not necessarily guarantee treatment for pregnant women or their partners.